PENGEMBANGAN CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL TRADISI TOLAK BALA ALA SUKU DAYAK UNTUK SISWA SEKOLAH DASAR - Margareth Febi Patrizki Dami; Susanto, Moh. Rusnoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Local wisdom has been included in the 2013 elementary school curriculum thematic learning. Based on interviews conducted by researchers with fifth grade teachers at Muhammadiyah Tamantirto Elementary School, researchers received information that currently teachers are getting students used to creating stories and literacy materials in the library still do not provide many visuals about culturally based picture stories. Therefore, researchers developed the video "The Tradition of Rejecting Bala in the Dayak Tribe" as a literacy tool for class V to introduce one of the traditions that exist in West Kalimantan. The aim of this research is to describe the steps for the development and quality of ceramics. The type of research used is research and development (R&D) ADDIE model as a development procedure according to Tung (2017), namely: (1) analysis, carried out by researchers using unstructured interviews, (2) design, carried out by researchers by studying supporting theories and making a cergam grid, (3) development, carried out by researchers by making cergams, (4) implementation, carried out after improving the product from validator suggestions and carrying out cergam trials on class V students, (5) evaluation, namely analyzing student responses towards the picture story being developed. This development resulted in the majority of students responding well to the bergmaabar story and increasing their knowledge about one of the Dayak tribal traditions of repelling reinforcements.